DAMPAK GIZI PADA PERKEMBANGAN KOGNITIF ANAK: KAJIAN LITERATUR DAN TEMUAN BARU - Afni, Fauza; Zulfan Zulfikar; Nur Rohmah; Muhammad Toat; Rauza Sukma Rita (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2025)
Children's cognitive development is an important aspect in their growth stage, which can be influenced by a variety of factors including nutrition. This article aims to investigate the impact of nutrition on children's cognitive development through an in-depth literature review and presentation of new findings. We conducted a careful literature search to identify the latest studies relating to the relationship between nutrition and children's cognitive development. In this article, we summarize the results of studies that support a positive relationship between good nutritional intake and optimal cognitive development in children. We also present new findings that underscore the importance of proper nutrition in critical stages of cognitive development. We highlight the role of key nutrients, such as omega-3 fatty acids, certain vitamins and minerals, in children's cognitive development. In addition, we discuss the implications of nutrition policies and practices that can help improve children's cognitive development. This research provides valuable insights for parents, educators, and health professionals in understanding the importance of nutrition in supporting children's cognitive development. The new findings in this study could lay the foundation for improved nutrition programs and interventions aimed at maximizing children’s cognitive potential